2019
DOI: 10.1002/cpmo.66
|View full text |Cite
|
Sign up to set email alerts
|

Designing a QTL Mapping Study for Implementation in the Realized Collaborative Cross Genetic Reference Population

Abstract: The Collaborative Cross (CC) mouse resource is a next‐generation mouse genetic reference population (GRP) designed for high‐resolution mapping of quantitative trait loci (QTL) of large effect affecting complex traits during health and disease. The CC resource consists of a set of 72 recombinant inbred lines (RILs) generated by reciprocal crossing of five classical and three wild‐derived mouse founder strains. Complex traits are controlled by variations within multiple genes and environmental factors, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The present study was undertaken to challenge this assumption by using a genotyped and defined population of CC mouse lines previously shown to allow the determination of the heritability of a test trait employing a relatively low number of mice lines. 25,39 Polyphenol-rich cranberry extract was used as a source of food supplement because it holds the premise to influence obesity in a limited study. For example, in one study it was found that the multi-component polyphenol-rich extract obtained from cranberries could have a beneficial effect on the prevention or treatment of obesity via the inhibition of adipogenesis, lipid accumulation, and reactive oxygen species (ROS) production in adipocytes without affecting their viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was undertaken to challenge this assumption by using a genotyped and defined population of CC mouse lines previously shown to allow the determination of the heritability of a test trait employing a relatively low number of mice lines. 25,39 Polyphenol-rich cranberry extract was used as a source of food supplement because it holds the premise to influence obesity in a limited study. For example, in one study it was found that the multi-component polyphenol-rich extract obtained from cranberries could have a beneficial effect on the prevention or treatment of obesity via the inhibition of adipogenesis, lipid accumulation, and reactive oxygen species (ROS) production in adipocytes without affecting their viability.…”
Section: Discussionmentioning
confidence: 99%
“…The biological replica (number of mice per line and sex) used in this study was an excellent resource, which allowed performing a strong statistical analysis and calculating heritability and genetic covariance, and met the requirements as suggested earlier. 25,39 We anticipate that by increasing the number of assessed CC lines (30 lines and up) with an appropriate number of mice per line, 17 and by using the multi-trait and the multilocus analytical methods developed specifically for this genetically highly diverse reference population, 41 we will be able to map a genetic quantitative trait loci (QTL) with unprecedented precision to allow identification of genes associated with the ability of a particular food supplement to function in reducing weight. Because most mouse genes have orthologous genes in humans, we may be able to personalize the use of food supplements to function in reducing BW in humans.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The relationship of Tenm4 mutations and morphine tolerance may be worth researching in future investigations. However, owing to the limited number of GD strains used in this study, the QTL analysis is not obviously significant 34,35 . To confirm the exact role of these genetic loci in individual differences in morphine analgesia, much work remains to be done and more strains of GD mice need to be tested following this preliminary work.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the limited number of GD strains used in this study, the QTL analysis is not obviously significant. 34,35 To confirm the exact role of these genetic loci in individual differences in morphine analgesia, much work remains to be done and more strains of GD mice need to be tested following this preliminary work. Meanwhile, GD mice may play an increasingly important role as a new resource in the study of individual differences in drug responses.…”
Section: Quantitative Trait Locus Analysismentioning
confidence: 99%
“…There are several types of highly recombinant populations that can be used for rodent QTL studies that have gained traction in recent years due to advances in genotyping technology and statistical techniques [ 90 ]. They include heterogeneous stocks (such as the heterogeneous stock (HS) rat and mouse populations), hybrid diversity panels (such as the Hybrid Rat Diversity Panel (HRDP) and Hybrid Mouse Diversity Panel (HMDP)), recombinant inbred (RI) strains (such as the BXD, LXS, and CC panels), and commercially available outbred stocks (such as CFW mice and Sprague Dawley rats) [ 62 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Heterogeneous stocks and commercially available outbred populations are generally created by semi-random breeding strategies that maximize genetic diversity while maintaining favorable minor allele frequencies (e.g., >10%).…”
Section: Genetic Approaches In Rodent Models Of Audsmentioning
confidence: 99%